MiR-30a suppresses non-small cell lung cancer progression through AKT signaling pathway by targeting IGF1R - Wen, X. P; Ma, H. L; Zhao, L. Y; Zhang, W; Dang, C. X (Cellular and Molecular Biology, 2015)
MicroRNAs play critical roles in the development and progression of human cancers. Although miR-30a has been suggested to function as a tumor repressor in several tumors, its role in non-small cell lung cancer (NSCLC) has not been investigated in detail. This study investigated the expression and role of miR-30a in human NSCLC. The expression of miR-30a is significantly decreased in clinical NSCLC tissues and cell lines. Overexpression of miR-30a inhibited NSCLC cell proliferation, G1/S and S/G2 transition in vitro, whereas suppression of miR-30a facilitated NSCLC cell proliferation, G1/S and S/G2 transition. Using a luciferase reporter assay, insulin-like growth factor 1 receptor (IGF1R) was determined to be a direct target of miR-30a. Furthermore, silencing IGF1R resulted in the same biologic effects of miR-30a overexpression in NSCLC cells, which included suppressed NSCLC cell proliferation and trigering cell cycle arrest through PI3K/AKT signaling pathway by inhibiting cell cycle regulators (CDK2, CDK4, Cyclin A2 , Cyclin D1). These results demonstrate that miR-30a influences NSCLC progression through PI3K/AKT signaling pathway by targeting IGF1R in A549 cells, which suggest miR-30a as a novel strategy for NSCLC diagnosis and treatment.